Birefringence of InₓTl₁₋ₓI solid state solution - Kashuba, A.I.; Franiv, A.V.; Bovgyra, O.V.; Brezvin, R.S. (Functional Materials, 2017)
The results of investigation of optical properties of the newly synthesized solid solution InₓTl₁₋ₓI in concentration range of 0.4≤x≤0.7 are presented. Birefringence is measured for InₓTl₁₋ₓI solid state solution. Dependence of the birefringence Δ ni on the concentration of thallium iodide is investigated. Dielectric permeability distribution ε(E) is calculated using pseudopotential method in the framework of density functional theory. The real ε₁ and imaginary ε₂ parts of the dielectric constant are calculated for polarization E